Economic Valuation of the Klapanunggal Karst Region Using the Travel Cost Method - Jamaludin, Jamaludin; Mizuno, Kosuke; Rizal, Reda (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2024)
Indonesia has Karst areas spread throughout almost the entire archipelago. The Klapanunggal Karst region has been officially designated as a Karst Landscape Area, to emphasize its protected status, in alignment with governmental endeavors aimed at ensuring the long-term preservation of the ecological and human-related significance of this karst ecosystem. The aim of this research is to perform an economic valuation of the Klapanunggal Karst region using the Travel Cost Method. The research conducted intensive field observations within the Klapanunggal Karst area and administered well-structured questionnaires to a sample size of 109 respondents from visitor Klapanunggal Karst region. Base on observations and field data, the Klapanunggal Karst region was partitioned into four distinctive zones. Zone 1 is location within an industrial limestone mining permit area, thus vulnerable to the imminent threat of industrial mining activities. Zone 2 is situated within the precincts of the Klapanunggal KBAK. Zone 3 has been transformed from a former mining site into a tourist destination. Lastly, Zone 4 has earned the coveted status of a tourist village. Subsequently, based on the economic valuation calculations, the Klapanunggal Karst region was found to have an annual economic value of Rp. 4,156,219,112.40, with a visitation rate of 0.006% of the total tourists visiting Bogor Regency. The researchers also recommend the development of tourism in the Klapanunggal Karst region as a means of enhancing the local economy, as well as ensuring the protection and sustainability of the Klapanunggal Karst area, including other critical aspects like water resources and ecosystem values.